2017
DOI: 10.1159/000486123
|View full text |Cite
|
Sign up to set email alerts
|

Benzotriazole Enhances Cell Invasive Potency in Endometrial Carcinoma Through CTBP1-Mediated Epithelial-Mesenchymal Transition

Abstract: Background/Aims: Benzotriazole (BTR) and its derivatives, such as intermediates and UV stabilizers, are important man-made organic chemicals found in everyday life that have been recently identified as environmental toxins and a threat to female reproductive health. Previous studies have shown that BTR could act as a carcinogen by mimicking estrogen. Environmental estrogen mimics could promote the initiation and development of female cancers, such as endometrial carcinoma, a type of estrogenic-sensitive malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…ADAM17 is activated by PC furin with subsequent induction release of TNF‐α 75 . Higher ADAM17 expression is linked with the development of EAC 77 . Xu and coworkers found that a high level of ADAM17 was associated with poor clinical outcomes in women with uterine carcinoma 78 .…”
Section: Furin and Eacmentioning
confidence: 99%
“…ADAM17 is activated by PC furin with subsequent induction release of TNF‐α 75 . Higher ADAM17 expression is linked with the development of EAC 77 . Xu and coworkers found that a high level of ADAM17 was associated with poor clinical outcomes in women with uterine carcinoma 78 .…”
Section: Furin and Eacmentioning
confidence: 99%
“…The cytotoxicity profiles of the MSC-CDs were studied in RAW 264.7 cells using a CCK-8 assay [26]. The cells were cultured in Dulbecco's modified Eagle's medium supplemented with 20% foetal bovine serum in a humidified 5% CO 2 atmosphere at 37 C. The RAW 264.7 cells were counted and seeded in 96-well plates at a density of 1 Abs sample and Abs control represent the A450 of the experimental and control groups, respectively.…”
Section: In Vitro Cytotoxicity: Cck-8 Assaymentioning
confidence: 99%
“…3 These chemicals are ineffectively removed by traditional wastewater treatment plant (WWTP) processes [4][5][6][7][8] and have adverse impacts (e.g., endocrine disrupting effects) on aquatic organisms according to in vitro and in vivo tests; 3,9,10 additionally, benzotriazoles exhibit carcinogenicity and genotoxicity. 11,12 Among all benzotriazoles and benzothiazoles, benzotriazole (BT) and benzothiazole (BTH) are the two representative examples. The intrinsic physicochemical profiles of BT and BTH are presented in Table S1.…”
Section: Introductionmentioning
confidence: 99%